The Relationship Between Manufacturing Flexibility and Performance: A Meta Analytical Study - Avunduk, Huseyin (International Journal of Contemporary Economics and Administrative Sciences, 2018)
Today, manufacturing industries are trying to maintain and increase their competitiveness in an environment where constantly changing uncertainty prevails. The industry is increasingly searching for new technology to respond quickly and at low cost to fluctuating customer demands in the market. Manufacturing flexibility has become one of the prime areas of research in manufacturing technology. In the literature studies investigating the relationship between manufacturing flexibility and different aspect of performance are seen to yield differing results, and we are forced to consider that there might be other factors influencing this relationship. In this study an attempt was made to reveal the relationship between manufacturing flexibility and performance by means of a meta analysis of the combined results of separate studies carried out between 1990 and 2017 using an analytical technique.The resulting meta-analytical results are in line with the results of previous individual studies. The meta analysis findings have revealed a positive relationship between Advanced Manufacturing Technologies (AMT), Engineering Technologies (ET) and types of Administration Technologies (AT) on one side and production and overall performance on the other. Evaluations of the findings obtained in the study are presented.